x+(y+z)=(x+y)+z by taking x=-3/4,y=4/-7and z=-5/-4

Question

x+(y+z)=(x+y)+z by taking
x=-3/4,y=4/-7and z=-5/-4

in progress 0
Valentina 3 weeks 2021-10-01T20:25:25+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-01T20:26:40+00:00

    Answer:

    Verify x+(y+z)=(x+y)+z for the following values of x,y,z (i)x=3/4,y=5/6,z=-7/8(ii)x=2/3,y=-5/6,z=-7/9(iii)x=3/5,y=-6/9,z=2/10(iv)x=-3/5,y=-7/10,z=-8/15

    To Verify x+(y+z)=(x+y)+z

    (i)x=3/4,y=5/6,z=-7/8

    LHS = 3/4 + (5/6 + (-7/8)) = (3/4) + (5/6 -7/8) = (3/4) + ((20 – 21)/24) = 3/4 – 1/24

    = (18 – 1)/24 = 17/24

    RHS = (3/4 + 5/6) + (-7/8) = (9 + 10)/12 – 7/8 = 19/12 – 7/8 = (38 – 21)/24 = 17/24

    LHS = RHS = 17/24

    (ii)x=2/3,y=-5/6,z=-7/9

    LHS = 2/3 + (-5/6 + (-7/9) = 2/3 + ( -5/6 – 7/9) = 2/3 + (-29/18) = 2/3 – 29/18

    = 12/18 – 29/18 = -17/18

    RHS = (2/3 + (-5/6) ) + (-7/9) = (2/3 – 5/6) – 7/9 = (-1/6) – 7/9 = -1/6 – 7/9 = -3/18 – 14/18 = -17/18

    LHS = RHS

    Step-by-step explanation:

    I hope it helps you

    mark me BRANLIST please

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )